From theory to experiment: hadron electromagnetic form factors in space-like and time-like regions - Tomasi-Gustafsson, E.; Gakh, G.I.; Rekalo, A.P. (Вопросы атомной науки и техники, 2007)
Hadron electromagnetic form factors contain information on the intrinsic structure of the hadrons. The pioneering work developed at the Kharkov Physical-Technical Institute in the 60's on the relation between the polarized cross section and the proton form factors triggered a number of experiments. Such experiments could be performed only recently, due to the progress in accelerator and polarimetry techniques. The principle of these measurements is recalled and surprise and very precise results obtained on proton are presented. The actual status of nucleon electromagnetic form factors is reviewed, with special attention to the basic work done in Kharkov Physical-Technical Institute. This paper is devoted to the memory of Prof. M.P. Rekalo.